Parental Attitudes and Childhood Traumas as Predictors of Obsessive–Compulsive Symptoms in University Students - Kacan, Havva; Öztürk, Ayfer (AVES YAYINCILIK A.Ş., 2023)
In this study, we aimed to examine the predictive effects of parental attitudes and childhood traumas on obsessive-compulsive symptoms in university students.This cross-sectional and correlational study was performed with the participation of 780 students. The data collection tools were a "Descriptive Information Form," the "Padua Inventory," the "Childhood Trauma Questionnaire-28," and the "Parental Attitude Scale."The results of the regression analysis revealed that perceived protective/demanding (ß = 0.959; P < .001) and authoritarian (ß = 0.439; P < .001) parenting attitudes and childhood traumas (emotional neglect ß = 0.905; P = .049; physical abuse ß = 1.464; P = .002; emotional abuse ß = 2.152; P < .001; sexual abuse ß = 0.812; P = .030) constituted a positive and significant predictor of obsessive-compulsive symptoms.Evaluation of parental attitudes and childhood traumas and interventions aimed at predicting the obsessive-compulsive disorder-related consequences of parental attitudes and childhood traumas can help alleviate obsessive-compulsive disorder symptoms. Involving families in treatment approaches such as psychoeducation and psychotherapy for childhood trauma victims with obsessive-compulsive disorder and cooperation with families can positively affect treatment processes. Nurses with the roles of direct care, support, education, and counseling have important standing in running psychoeducation groups. In particular, academic psychiatric nurses can identify risky students and provide counseling and psychoeducation to university students.
Keywords: Experiences; Behaviors; Avoidance; Disorder; Neurosciences. Biological psychiatry. Neuropsychiatry; Original Article; Reliability; Abuse; Dissociation; Severity; Validity; RC321-571